Penerapan Model Pembelajaran Cooperative Learning Tipe TGT (Teams Games Tournament) Berbantuan Media Word Square Dalam Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Ekonomi - Ulpah, Yunita Dena; Nurdianti, Raden Roro Suci; Afriza, Edi Fitriana (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
The low learning outcomes of students at SMA Negeri 1 Cihaurbeuti in economic subjects are a problem that occurs. The experimental method is used as a way to solve the above problems, with a research design using a non-equivalent control group design. The population of this study were all XI social studies classes at SMA Negeri 1 Cihaurbeuti in the 2024/2025 academic year which amounted to 170 students. The sample used was class XI IPS 2 which amounted to 36 people as a control class and class XI IPS 4 which amounted to 36 people as an experimental class with sampling using nonprobability sampling technique. Based on the results of research that has been done where Ha is accepted if the sig.(2-tailed) value <0.05 and based on research obtained sig.(2-tailed) value <0.05. The average value on the experimental class score is higher than the control class, thus it can be concluded in this study that the Cooperative Learning Model type TGT (Teams Games Tournament) assisted by Word Square Media can improve student learning outcomes. Translated with DeepL.com (free version)